Physiological factors which influence the performance potential of athletes: analysis of sports medicine performance testing in Nordic combined - Schupfner, R.; Pecher, S.; Pfeifer, E.; Stumpf, C. (The Physician and Sportsmedicine, 2021)
Background The sports medicine performance diagnostics include investigative procedures that supply information on the performance capacity and stamina of an athlete. This creates a foundation for a personalised training plan and enables optimised control of the training process.